2020
DOI: 10.1177/1091581820939081
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1-Induced COX-2 Expression Promotes Mitophagy and Contributes to Lipid Accumulation in Hepatocytes In Vitro and In Vivo

Abstract: Aim: Aflatoxin B1 (AFB1) is hepatotoxic. Numerous studies have shown that mitochondria play an essential role in AFB1-induced steatosis. However, the mechanisms of AFB1-induced steatosis via mitochondria are still obscure. The present study aimed to confirm that AFB1 causes hepatocyte steatosis regulated by cyclooxygenase-2 (COX-2)-induced mitophagy, both in vivo and in vitro. Methods: Adult male C57BL/6 mice were randomly divided into control group with the same volume of peanut oil and exposure group adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…On basis of AFs-induced mitochondrial damage, for selective autophagy, mitophagy is the sequestration of damaged mitochondria by autophagosomes, which display loss of membrane potential. Both in vitro and in vivo studied indicate that AFB 1 promotes mitophagy by increased Parkin and PTEN-induced putative kinase 1 (PINK1) through inducing the expression of COX-2, then results in lipid accumulation and steatosis, due to the fact that mitophagy disrupts the normal mitochondrial lipid metabolism function ( Ren et al, 2020 ). But in consideration of positive role of mitophagy in removing damaged mitochondria and maintaining its quality and metabolism, more explicit evidences about AFs-induced mitophagy in hepatotoxicity need to be excavated.…”
Section: Afs Aggravate Hepatotoxicity Via the Destruction Of Survivalmentioning
confidence: 99%
“…On basis of AFs-induced mitochondrial damage, for selective autophagy, mitophagy is the sequestration of damaged mitochondria by autophagosomes, which display loss of membrane potential. Both in vitro and in vivo studied indicate that AFB 1 promotes mitophagy by increased Parkin and PTEN-induced putative kinase 1 (PINK1) through inducing the expression of COX-2, then results in lipid accumulation and steatosis, due to the fact that mitophagy disrupts the normal mitochondrial lipid metabolism function ( Ren et al, 2020 ). But in consideration of positive role of mitophagy in removing damaged mitochondria and maintaining its quality and metabolism, more explicit evidences about AFs-induced mitophagy in hepatotoxicity need to be excavated.…”
Section: Afs Aggravate Hepatotoxicity Via the Destruction Of Survivalmentioning
confidence: 99%
“…The results indicated that treatment with M2 reduces the formation of AFB 1 -DNA adducts and MDA in liver tissue, thus alleviating liver damage. AFB 1 is hepatotoxic and is a significant factor in promoting the development of primary hepatocellular carcinoma (HCC) [ 5 ]. Moreover, other studies reported that BACH1 is upregulated in HCC samples, with BACH1 facilitating the growth and metastasis of HCC [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The toxic effects of AFB 1 are both dose- and time-dependent, and aflatoxicosis can be either acute or chronic. Exposure to AFB 1 affects multiple organs like kidneys, liver, heart, testes, and ovaries, causing mutagenesis, growth retardation, and reproductive damage [ 5 , 6 ]. Moreover, AFB 1 toxicity significantly suppresses the immune system, increasing the risk of acquiring concurrent infectious diseases [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data indicated that mitophagy may play a protective role during AFB1-exposure-induced adverse effects in animals or humans. Additionally, a previous study found that AFB1 exposure at a dose of 0.6 mg/kg for 28 days could significantly alter the expression of PINK1, Parkin, and COX-2, and the knockout of COX-2 significantly inhibited AFB1-induced mitophagy [ 159 ]. COX-2 also play critical roles in a variety of pathological processes, including cell proliferation, ferroptosis, inflammatory reaction, and apoptosis [ 159 ].…”
Section: Curcumin’s Protective Role In Preventing Afb1-induced Toxici...mentioning
confidence: 99%